RYGB increases the satiating effect of intrajejunal lipid infusions in female rats. (1st December 2018) - Bächler, Thomas; Geary, Nori; Bueter, Marco; Leeners, Brigitte; Rehfeld, Jens F.; Lutz, Thomas A.; Asarian, Lori
Abstract: We used a novel rat model to investigate the physiological bases of early satiation after Roux-en-Y gastric bypass surgery (RYGB). Female rats were subjected to RYGB or sham surgery. Chronic infusion catheters were placed in the Roux limb of RYGB rats and the corresponding anatomical locus of the jejuna of sham-RYGB rats. Rats were also ovariectomized and chronically treated with either estradiol (E2; 2 μg each 4th day SC) or the oil vehicle. Testing was begun 10–12 wk after surgery. Intrajejunal lipid infusions (10 min, 4.4 mL, 8.8 kcal) were performed just before test meals of a low-energy artificially sweetened gel diet (0.1 kcal/g) that RYGB rats ingest avidly. Intrajejunal lipid infusions reduced test-meal size more in RYGB rats than sham-operated rats, indicating that, at least after prolonged adaptation to surgery, the satiating actions of lipids acting intra- or post-jejunally are increased by RYGB and that accelerated meal appearance in the intestines after RYGB is not necessary for this effect. The satiating effects of intrajejunal lipid infusions were similar in E2-and oil-treated rats, suggesting that the effect was not dependent on an activational effect of estrogens. In a second experiment, pretreatment with the cholecystokinin A-receptor antagonist devazepide reduced the satiating effect of intrajejunal lipid infusions in E2-treated RYGB rats. Although these data are preliminary due to the smaller numbers of rats than in the first experiment, they suggest that cholecystokinin-mediated jejunal satiation contributes to early satiation after RYGB in ovariectomized rats with peri-ovulatory levels of estradiol. The results of these experiments may be relevant to understanding RYGB outcome in pre- and postmenopausal women.